Optical properties and fine faulty structure of sapphire crystals grown in low pressure CO gas atmosphere - Puzikov, V.M.; Danko, A.Ya.; Adonkin, G.T.; Sidelnikova, N.S.; Tkachenko, V.F.; Budnikov, A.T. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Presented in this paper are the results of the study of optical characteristics and fine faulty structure of big sapphire crystals grown in a CO-based low pressure (0.1...0.3 torr) gas atmosphere. Optimal conditions for annealing optical elements of such crystals have been determined. They provide high transparency of crystals in the UV region and their high resistance to the UV radiation. A perspectivity of using CO medium for growing big sapphire crystals of high optical and structure quality has been confirmed.